Delineating caveats for (quality) education during displacement: Critiquing the impact of forced migration on access to education. (3rd June 2019) - Benhura, Abigail Rudorwashe; Naidu, Maheshvari
Abstract: This qualitative article aims at unraveling the impact of displacement on the access to (quality) education. The article is premised on the inherent role played by education to equip displaced children with functional skills and act as a liberating force in the face of forced displacement. Using purposive homogeneous sampling from Hopley and Caledonia settlements for internally displaced people (Zimbabwe), the article attempts to evaluate effects of displacement on the quality of education or access thereof. The article uses inter-textuality as a method to complement empirical evidence with reviewed literature. The Capability Approach is applied to assess the implications of forced migration on the provision of (quality) education. In terms of the Capability Approach, quality education is measured through the actual achievements realised by any human being who has been exposed to it (education). Therefore, the Capability Approach posits that every human being has the inherent potential to be who they aspire to be when exposed to a conducive environment. In the context of this article, access to quality education is an enabling environment. The findings indicate that displacement is invariably detrimental to the provision of quality education. Moreover, this condition enhances the vulnerabilities of forced migrants as education is critical, instrumental, and of intrinsic value to the socio-economic development of its recipients. This being so, the impact of displacement on internally displaced persons' access to quality education is a topical issue worthy of discussion so as to chart relevant solutions to the varying contexts of displacement.